Approaches to post-mining land reclamation in polish open-cast lignite mining = Rekultywacja terenów pogórniczych w polskim górnictwie odkrywkowym węgla brunatnego - Kasztelewicz, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the situation regarding the reclamation of post-mining land in the case of particular lignite mines in Poland until 2012 against the background of the whole opencast mining. It discusses the process of land purchase for mining operations and its sales after reclamation.
Keywords: kopalnie odkrywkowe węgla brunatnego; rekultywacja; rewitalizacja; zagospodarowanie terenów; lignite open-cast mining; reclamation; revitalisation; land management